2018
DOI: 10.1177/1045389x18786464
|View full text |Cite
|
Sign up to set email alerts
|

Approximation of surface wave velocity in smart composite structure using Wentzel–Kramers–Brillouin method

Abstract: In mathematical physics, the Wentzel–Kramers–Brillouin approximation or Wentzel–Kramers–Brillouin method is a technique for finding approximate solutions to linear differential equations with spatially varying coefficients. An attempt has been made to approximate the velocity of surface seismic wave in a piezo-composite structure. In particular, this article studies the dispersion behaviour of Love-type seismic waves in functionally graded piezoelectric material layer bonded between initially stressed piezoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Among the three types of waves, namely, the body torsional waves, the Rayleigh waves, and Love waves, the body waves decay quickly over distance so the total area of severe damage caused by the body waves is much smaller than the Rayleigh and the Love waves, which are surface waves. [31][32][33][34][35] Between the Rayleigh waves that reside in thick soil and the Love waves that reside in shallow soil above bed rock, the Rayleigh waves are more often encountered than Love waves because in geology thick soil cites are more common than shallow soil. Furthermore, once the means to attenuate Rayleigh waves are established, they could serve as a reference for the Love waves.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…Among the three types of waves, namely, the body torsional waves, the Rayleigh waves, and Love waves, the body waves decay quickly over distance so the total area of severe damage caused by the body waves is much smaller than the Rayleigh and the Love waves, which are surface waves. [31][32][33][34][35] Between the Rayleigh waves that reside in thick soil and the Love waves that reside in shallow soil above bed rock, the Rayleigh waves are more often encountered than Love waves because in geology thick soil cites are more common than shallow soil. Furthermore, once the means to attenuate Rayleigh waves are established, they could serve as a reference for the Love waves.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…In the area of structures and materials, wave propagation-based tools have found increasing applications, especially in structural health monitoring and active control of vibrations and noise (Achenbach, 1973). Regarding the analysis of traveling plane waves across structures consisting of piezoelectric and FGM elements, there are several studies in the literature (Abad and Rouzegar, 2019; Berezovski et al, 2003; Chaudhary et al, 2017, 2018, 2019; Eskandari and Shodja, 2008; Nirwal et al, 2019; Qian et al, 2008; Sahu et al, 2018; Saroj et al, 2019; Singh et al, 2018; Singhal and Sahu, 2017; Singhal et al, 2018a, 2018b, 2019a, 2019b). As notable examples, Singhal et al (2018a, 2018b) used Wentzel-Kramers-Brillouin (WKB) and Liouville-Green (LG) analytical approaches to study surface waves in piezoelectric composite structures.…”
Section: Introductionmentioning
confidence: 99%
“…Different investigations are available in literature focusing on the mechanical behaviors of piezoelectric nanostructures [3,4] on fields of linear and nonlinear, longitudinal and transverse, free and forced wave propagation in microscale. Initial and couple stress influence on transmission of the Love-type wave [5], and Rayleigh waves [6] in material layers with imperfect interface [7], and surface wave propagation between viscous liquid and initially stressed piezoelectric half-space [8] are investigated by using the spatial varying WKB (Wentzel-Kramers-Brillouin) method [9,10]. Solutions are obtained by a perturbation technique in closed-form for normal, shear stresses, dielectric displacement, and electric potential [11], and it is found that the complex phase velocity with positive imaginary part increases with time [12].…”
Section: Introductionmentioning
confidence: 99%